Population and Public Health Implications of Child Health and Reproductive Outcomes Among Carrier Couples of Sickle Cell Disorders in Madhya Pradesh, Central India - Ranbir S. Balgir, PhD (Global Health and Education Projects, Inc., 2014)
Background: Sickle cell disease is a major genetic and public health challenge in India. Adequate studies on clinico-hematological aspects of disorders are available, however there are few studies on the public health and reproductive outcomes among sickle cell carrier couples. Methods: A total of 383 couples including their offspring with at least one case of sickle cell disorder referred to a testing center from a tertiary hospital from March 2010 to February 2013 were consecutively studied as matched case controls. Results: Out of 383 couples, 200 were found normal and 183 had different sickle cell disorders. Carrier couples of sickle cell disease had significantly higher fertility (mean number of conceptions, i.e. 3.153 versus 1.480) and higher below 10 year mortality (11% versus 2.7%) and lower surviving offspring (877.4 versus 970.6) than of controls. Neonatal and infant mortality was doubled (34.3 versus 14.7) and three-fold higher (44.1 versus 14.7), respectively in carriers of disease per 1000 live-births compared to controls. Couples of AS/SS genotype showed high neonatal, infant, below 10 year mortality (214.3 each) and low surviving offspring (785.7 per 1000 live-births). Conclusions and Global Health Implications: Sickle cell carrier couples are increasing in both trait and disease offspring (surviving: 56.7% against 43.3% normals). This increased production of carrier and disease offspring leads to increased morbidity, neonatal/infant and childhood mortality, and adversely affects the survival fitness.